Development of the KOUTI GPS Tamper-Resistant Monitoring System for Preventing Fuel Distribution Fraud in Tanker Trucks - Syafrie, Muh.; Agung Apriyanto, Taufik; E Kumindang, Ridnal; Herman, Herman; Wasiu Akande, Ahmed (Jurusan Pendidikan Teknik Elektro, 2026)
The integrity of the fuel distribution system is highly dependent on the reliability of Global Positioning System (GPS) monitoring devices used to track tanker truck movements in real time. However, in operational practice, GPS devices are still vulnerable to physical manipulation, removal, and other disturbances, which can reduce the validity of the monitoring data and increase the risk of distribution deviations. This study uses an engineering development and implementation approach to design, prototype, and evaluate KOUTI GPS, a tamper-resistant monitoring system that integrates a mechanical protective cover, a micro switch sensor for unauthorized opening detection, and real-time notification on the fleet monitoring dashboard. The system was implemented on [n] tanker trucks for [x] days/week and evaluated through material testing, functional testing, system integration testing, operational simulation, and performance testing. The evaluationindicators included GPS positioning accuracy, disturbance detection response time, signal stability, data validity, and system reliability. The test results show that the system is able to maintain position accuracy deviations up to ±5 m, generate disturbance alerts in less than 1 swhen the box is opened, display real-time notification integration, and maintain 100% data validity without significant system disruptions during the monitoring period. Compared with conventional fleet monitoring systems that typically emphasize software-based tracking, KOUTI GPS offers a device-level approach through the integration of physical protection and real-time tamper detection. These findings suggest that this approach has the potential to improve monitoring integrity and operational transparency in fuel distribution and could be considered for other fleet applications requiring a more secure GPS infrastructure.